2020
DOI: 10.1111/jfpp.14489
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: Antibacterial activity and mechanism of Tetrapleura tetraptera stem extract against Salmonella strains and its application in raw chicken meat

Abstract: Poultry meat is one of the most valuable protein sources for human consumption. It is a combination of muscle tissue, attached skin, connective tissue and edible organs of avians, which are commonly used for food. Chicken meat accounts for about twothirds of the world's total consumption (Ruban, Thiyageeswaran, & Sharadha, 2010). Salmonella is a gram-negative, facultative anaerobic bacteria, belonging to the family of Enterobacteriaceae (Afshari, Baratpour, Khanzade, & Jamshidi, 2018). Salmonella contamination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Elsewhere, inhibition zones of 8 mm have been reported and 13 mm for 2.5 mg/mL and 5.0 mg/mL, respectively, of essential oil M. myristica against E. coli 3 , whereas 11 mm for 2 mL also of M. myristica essential oil against E. coli 26 . Another study showed T. tetraptera stem extract against two Salmonella strains, with a remarkably high inhibition zone (> 20 mm diameter) 10 , besides the absence of carvone component believed as responsible for the weak activity of oleoresins 27 , 28 . Comparatively, the promising antibacterial activity of essential oil from M. myristica might be dependent on factors like chemical composition and its solubility 3 .…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Elsewhere, inhibition zones of 8 mm have been reported and 13 mm for 2.5 mg/mL and 5.0 mg/mL, respectively, of essential oil M. myristica against E. coli 3 , whereas 11 mm for 2 mL also of M. myristica essential oil against E. coli 26 . Another study showed T. tetraptera stem extract against two Salmonella strains, with a remarkably high inhibition zone (> 20 mm diameter) 10 , besides the absence of carvone component believed as responsible for the weak activity of oleoresins 27 , 28 . Comparatively, the promising antibacterial activity of essential oil from M. myristica might be dependent on factors like chemical composition and its solubility 3 .…”
Section: Resultsmentioning
confidence: 97%
“…Probably, the presence of linalool might account for the plant’s peppery nature, whereas both γ-terpinene and α-thujene might account for the flavor/fragrance. Elsewhere, the root and stem ethanol extract of T. tetraptera spice respectively obtained 70.14% 25 and 32.01% 10 . Polyphenols like eugenol, quercetin, rutin, and tyrosol, according to Moukette et al .…”
Section: Resultsmentioning
confidence: 99%
“…The MIC was detected by the broth dilution method described by the previous study with some modifications (Agyemang et al . 2020). Firstly, 50 μl of different concentrations of extracts was added to each well of a 96‐well plate containing 50 μl of MH liquid medium.…”
Section: Methodsmentioning
confidence: 99%
“…Chicken is one of the most popular meats as it is a rich source of protein for human consumption ( Baek et al, 2020 ; Agyemang et al, 2021 ). In addition, chicken meat has the advantage of being lower in fat content and price, and there are less restrictions by religious dietary practices compared to red meats ( Ma et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%